‘You Can Be a Citizen of Mars: ‘Token of Passports’ Rituals, Overseas Travels, and Ghana’s Neo-Pentecostal Spaces - Dennis, Dorcas (Journal of religion in Africa, 2025)
This paper examines how a local Ghanaian Pentecostal church mediates global mobility and structural immigration barriers for alienated persons through ritual performance. Imperial alienating immigration processes for ‘undesired’ persons on the move to the Global North engender a religious ritual performance designed to confront the alienating structures, negotiate imposed dominant labels, and reconstruct belonging. In the ritual process, passports become sacred tools for mediating travel, while prophecies reveal travel constraints and future events. The ritual empowers and emboldens participants to pursue their travels as an orchestrated success program divinely prepared for them. The ritualization of travel is a symbolic performance of contestations of imperial travel barriers and alienations. Using data from ethnographic fieldwork at the Power Cathedral in Kumasi, popular for its innovative ‘Token of Passports’ (ToP) rituals, the article offers an account of the phenomenon in Ghana’s Pentecostal space to show how local religions mediate mobility for alienated groups.